Danger Is a Signal, Not a State: Bigaagarri—An Indigenous Protocol for Dancing Around Threats to Wellbeing - Phillip Orcher; Victoria J. Palmer; Tyson Yunkaporta (Social Sciences)
This paper describes the health and wellbeing applications of a protocol designed from a Gumbaynggirr Australian First People’s concept, Bigaagarri. The protocol reframes threats to health and wellbeing as part of a communicative system of environmental signals, rather than an individualised, behavioural fight–flight–fear response. Developed by a Muruwari Gumbaynggirr researcher, the protocol enfolds Aboriginal perspectives of health values and the physicality of personal location in place and social context. It combines Indigenous standpoint theory and lived-experience narrative research methods to translate Indigenous practices into generally accessible modalities. The paper connects the first principles of this protocol to literature, then, using code-switching between academic and informal settler and Indigenous voices, it introduces personal lived experience narratives that include utilisation of the participatory and immersive protocol seen in the graphical abstract image to mitigate suicidal ideation. This approach unsettles Westernised conceptions of health and wellbeing research that privilege disease-specific, single-solution approaches. It contests the dominant social imaginaries and narratives embedded in standard service models, which perpetuate the ongoing recolonisation of Indigenous identities, and common exclusion of others outside of the neurotypical majority. The Bigaagarri protocol is a potential way forward to reimagine preventive health landscapes, decolonise support for suicide and mental health through the embedding of Indigenous knowledges to lead to holistic approaches for wellbeing.